The Genomic Tree as Revealed from Whole Proteome Comparisons - Tekaia, Fredj (Cold Spring Harbor Laboratory Press, 1999)
The availability of a number of complete cellular genome sequences allows the development of organisms’ classification, taking into account their genome content, the loss or acquisition of genes, and overall gene similarities as signatures of common ancestry. On the basis of correspondence analysis and hierarchical classification methods, a methodological framework is introduced here for the classification of the available 20 completely sequenced genomes and partial information for Schizosaccharomyces pombe, Homo sapiens, and Mus musculus. The outcome of such an analysis leads to a classification of genomes that we call a genomic tree. Although these trees are phenograms, they carry with them strong phylogenetic signatures and are remarkably similar to 16S-like rRNA-based phylogenies. Our results suggest that duplication and deletion events that took place through evolutionary time were globally similar in related organisms. The genomic trees presented here place the Archaea in the proximity of the Bacteria when the whole gene content of each organism is considered, and when ancestral gene duplications are eliminated. Genomic trees represent an additional approach for the understanding of evolution at the genomic level and may contribute to the proper assessment of the evolutionary relationships between extant species.